Faktor – faktor yang Memengaruhi Perilaku Pencegahan Terhadap Paparan Thirdhand Smoke (THS) : A Systematic Literature Review - Aldyta Permata Sari; Nur Rohmah; Annisa Nurrachmawati (Jurnal Ners, 2026)
Thirdhand smoke (THS) refers to tobacco residue left on surfaces and in dust after cigarette smoke dissipates, posing health risks, especially to children. This study aims to identify and synthesize various factors influencing preventive behavior towards THS exposure through a systematic literature review. Articles were systematically searched in PubMed, Google Scholar, and Scopus for publications from 2021 to 2025, following the PRISMA 2020 guidelines and strict inclusion-exclusion criteria. Of the 280 identified articles, 12 studies (5,241 participants) were included, with most being cross-sectional and originating from Turkey. Key factors influencing THS prevention behavior included: awareness and knowledge (10 studies), belief in the dangers of THS (8 studies), education (6 studies), income (5 studies), smoking rules at home (5 studies), and smoking behavior (4 studies). Results showed that awareness of the term THS was low (8.7%), with higher education (OR=18.835; p<0.001) and homeownership (OR=2.667; p=0.004) significantly influencing beliefs about THS dangers. This study suggests public health interventions targeting THS education for lower-income and less-educated groups and recommends further research in diverse geographic and cultural contexts. Keywords: thirdhand smoke, THS, preventive behavior, awareness, knowledge.